-17-4=7n-6(2+n)

Simple and best practice solution for -17-4=7n-6(2+n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -17-4=7n-6(2+n) equation:


Simplifying
-17 + -4 = 7n + -6(2 + n)

Combine like terms: -17 + -4 = -21
-21 = 7n + -6(2 + n)
-21 = 7n + (2 * -6 + n * -6)
-21 = 7n + (-12 + -6n)

Reorder the terms:
-21 = -12 + 7n + -6n

Combine like terms: 7n + -6n = 1n
-21 = -12 + 1n

Solving
-21 = -12 + 1n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-1n' to each side of the equation.
-21 + -1n = -12 + 1n + -1n

Combine like terms: 1n + -1n = 0
-21 + -1n = -12 + 0
-21 + -1n = -12

Add '21' to each side of the equation.
-21 + 21 + -1n = -12 + 21

Combine like terms: -21 + 21 = 0
0 + -1n = -12 + 21
-1n = -12 + 21

Combine like terms: -12 + 21 = 9
-1n = 9

Divide each side by '-1'.
n = -9

Simplifying
n = -9

See similar equations:

| -(9x^2-3x+3)= | | y=n^2-2n-3 | | -3x-10=x+14 | | 6x-5=4x-27 | | f(x)=4x+3x-3 | | x^2+-12x+20= | | -2(-13+3y)-y=-5 | | -3+8=-5z+6(z+8) | | -6x+4+4x=2 | | -53=-6x-4x-3 | | -2(y+9)=-4y-22 | | 1+x+5x=73 | | 15a^2+21a-18=0 | | x^2+6x-55=equation | | x^3+3x^2-10x= | | 6+5u=-19 | | x/5=36 | | x/5=36 | | -1+2x-3x=-9 | | 15=x+2x-6 | | X+4-(6+3X-(5X-(8+X))-X)=0 | | 1/3b=3.52 | | 4x+6(8-3x)=8 | | 7p+3p=58-8 | | 2c+5=5c-7 | | 9(x-5)-8x=8 | | 2x-5=2(1.4x+3) | | 5+b-c=0 | | f(x)=-3x^2 | | 7x-7-6x=8 | | s^2+6s-1=0 | | x+10y=120 |

Equations solver categories